Common domains of nurses' competencies in public health emergencies: a scoping review - Xue-E. Guo; Li-Fang Bian; Yan Li; Chun-Yan Li; Yu Lin (BMC, 2023)
Abstract Background A public health emergency can cause large numbers of deaths in a short period, with devastating social, economic and health consequences. Nurses are the main healthcare providers during such emergencies, and their competencies affect the control and outcomes of the situation. Studies on nurses' competencies in public health emergencies vary between countries and healthcare systems. Therefore, we conducted a scoping review to identify the common domains of nurses' competencies in public health emergencies worldwide. Methods We searched the PubMed, CINHAL, Scopus, Web of Science, Science Direct, Embase, Cochrane Library, WanFang and ECRI databases from their inception to 2023. All published articles on nurses' competencies in public health emergencies that were published in English and Chinese were included. We mainly analyzed and synthesized nurses' competencies, assessment instruments and the training described in the included studies. Results A total of 27 competency domains were identified following an analysis and summary. The most frequently cited domains were communication skills, self-protection skills, basic knowledge of a public health emergency, laws and ethics and the capacity for organizational collaboration. The Disaster Preparedness Evaluation Tool and the Emergency Preparedness Information Questionnaire were the most commonly used tools for assessing competencies. Most training was conducted online and the content that was covered varied by country. Conclusions Given the significant roles and responsibilities of nurses in public health emergencies, knowing the domains of their competencies is essential to evaluating, developing, and conducting clinical training.